For all functions f , order these integrals from smallest to greatest:
A B C = ∫ 0 1 f ( x ) d x = ∫ 0 1 f ( x ) d x 1 = e ∫ 0 1 ln ( f ( x ) ) d x
Assume that all three definite integrals exist and converge to a finite value and that, for all x ∈ [ 0 , 1 ] , f ( x ) is defined and is positive.
If you believe that the order of A , B , C depends on function f , choose "None of the other options." Else, if you believe that A = B = C for all f satisfying the aforementioned restrictions, choose " A , B , C are always equal."
Bonus
Given that it has a unique inverse function f − 1 , what conditions does the function f have to satisfy such that f − 1 ( ∫ 0 1 f ( g ( x ) ) d x ) ≤ ∫ 0 1 g ( x ) d x for all functions g ( x ) ?
Again, assume that the definite integrals exist and converge to a finite value, and that g ( x ) is defined and is positive for all x ∈ ( 0 , 1 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That is incredibly neat. Nicely done.
Choose f(x)=1, then A=b-a and B=1/(b-a) and A=1/B
If b-a=A<1, then 1/A=B>1 and A<B. If b-a=a>1, then 1/A=B<1 and B<A.
Definition. Let U be a convex subset of a vector space over R . A function f : U ⟶ R is called convex just in case f ( p x + q y ) ≤ p f ( x ) + q f ( y ) for all convex linear combinations p x + q y , x , y ∈ U and p , q ∈ [ 0 , 1 ] , such that p + q = 1 .
Definition. Let U be a convex subset of a vector space over R . A function f : U ⟶ R is called concave just in case f ( p x + q y ) ≥ p f ( x ) + q f ( y ) for all convex linear combinations, p x + q y .
Lemma. Let U ⊆ R be convex and f : U ⟶ R be a C 2 function. Then a sufficient condition for convexivity (respectively concavity) of f is that f ′ ′ ≥ 0 (respectively ≤ 0 .
Proof. Clearly for trivial convex linear combinations, p x + q y , that is x = y or p = 0 or q = 0 , it holds that f ( p x + q y ) = p f ( x ) + q f ( y ) . Thus it suffices to consider convex linear combinations, p x + q y , with x = y and p , q = 0 and to show that f ′ ′ ≥ 0 be a sufficient condition for f ( p x + q y ) ≤ p f ( x ) + q f ( y ) . Wlog consider the case x < y . So in particular x < p x + q y < y .
It follows that
[ m c ] r c l f ( p x + q y ) − ( p f ( x ) + q f ( y ) ) = = = = p ( f ( p x + q y ) − f ( x ) ) + q ( f ( p x + q y ) − f ( y ) ) − p q ( y − x ) f ′ ( x ∗ ) + q p ( y − x ) f ′ ( x ∗ ) p q ( y − x ) ( f ′ ( y ∗ ) − f ′ ( x ∗ ) ) p q ( y − x ) ( y ∗ − x ∗ ) f ′ ′ ( c ) .
The final expression is ≥ 0 , since p , q > 0 , x < y , x ∗ < y ∗ and by the condition that f ′ ′ ≥ 0 . Hence f ( p x + q y ) − ( p f ( x ) + q f ( y ) ) ≥ 0 . Thus f is convex. A symmetric argument can be performed for convexity. QED
Examples. f = lo g ( ⋅ ) defined on ( 0 , ∞ ) is twice differentiable with f ′ ′ = − 1 / x 2 < 0 , hence concave. The function f = ⋅ − 1 defined on ( 0 , ∞ ) is twice differentiable with f ′ ′ = 2 / x 3 > 0 , hence convex.
Lemma (Jensen's Inequality). Let U ⊆ R be convex and X be a U -valued random variable. If f is a convex (respectively concave) function on U and both X , f ( X ) ∈ L 1 , then
f ( E [ X ] ) ≤ E [ f ( X ) ]
(respectively ≥ in the case of a concave function).
Proof (Sketch). Note that integrals are approximated by convex linear sums. Appealing to this and the property of convexivity (resp. concavity) yields the result. QED.
Corollary. Let X be a r. v. which is a.e. positive. Suppose X , 1 / X , lo g ( X ) are in L 1 . Then 1 / E [ 1 / X ] ≤ exp ( E [ lo g ( X ) ] ) ≤ E [ X ] . Proof. Since lo g is concave it holds by the above lemma that lo g ( E [ X ] ) ≥ E [ lo g ( X ) ] . By strict monotonicity of f = lo g ( ⋅ ) this implies E [ X ] ≥ exp ( E [ lo g ( X ) ] ) . Since 1 / X and lo g ( 1 / X ) = − lo g ( X ) are in L 1 , we get for free that
E [ 1 / X ] ≥ exp ( E [ lo g ( 1 / X ) ] ) = exp ( − E [ lo g ( X ) ] ) = 1 / exp ( E [ lo g ( X ) ] ) .
From this it follows that 1 / E [ 1 / X ] ≤ exp ( E [ lo g ( X ) ] ) . Hence the claim holds. QED.
Remark. In general one has that a sufficient condition for f − 1 E [ f ( X ) ] ≤ E [ X ] is that f be strictly monoton and concave, or that f be strictly antitone and convex. (See the above lemma and the above concrete example in the corollary.)
You should mention that the lemma you are using is Jensen's Inequality.
Log in to reply
I basically just derived that result on the spot, as the situation suggested it. But sure, I shall attribute the result appropriately, so that people can look it up.
Problem Loading...
Note Loading...
Set Loading...
Let's rewrite A , B , C using Riemann sums:
A = ∫ 0 1 f ( x ) d x = N → ∞ lim N 1 i = 0 ∑ N f ( N i )
B = ∫ 0 1 f ( x ) d x 1 = N → ∞ lim N 1 i = 0 ∑ N f ( N i ) 1 1 = N → ∞ lim i = 0 ∑ N f ( N i ) 1 N
C = e ∫ 0 1 ln ( f ( x ) ) = e N → ∞ lim N 1 i = 0 ∑ N ln ( f ( N i ) ) = e N → ∞ lim ln ⎝ ⎜ ⎛ N i = 0 ∏ N f ( a + N i ) ⎠ ⎟ ⎞ = N → ∞ lim N i = 0 ∏ N f ( N i )
Now, it should be obvious that A is the arithmetic mean of f ( N i ) for integers i = 0 to N , B is the harmonic mean, and C is the geometric mean. Since f ( x ) > 0 for all x ∈ [ 0 , 1 ] , by the AM-GM-HM inequality, we know that B ≤ C ≤ A , with equality occurring only and only when f ( x ) is a constant function almost everywhere for x ∈ [ 0 , 1 ] .